Social Safety Net Programs in Bangladesh: An Impact Study on Education, Health and Decision-Making Process of Women Beneficiaries - Islam, Md Nurul; Haque, Tawohidul; Mia, Md Tuhin (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Social Safety Net Programs (SSNPs) in Bangladesh, such as the Old Age Allowance (OAA) and Allowances for the Widowed, Deserted, and Destitute Women (AWDDW), aim to alleviate poverty and empower vulnerable populations, particularly women, by providing financial assistance to improve access to education, healthcare, and decision-making. Objectives: This study evaluates the impact of SSNPs on three key areas: (1) children’s education, (2) women’s health, and (3) their participation in household decision-making, aiming to identify areas for program improvement. Methods: A quantitative study was conducted with 180 women beneficiaries across Dhaka and Kurigram districts. Data was collected through structured questionnaires and analyzed using descriptive and inferential statistics in SPSS. Results: The study revealed that 65.6% of women beneficiaries had children currently studying, with 66.1% affirming that the allowance supported their education. A statistically significant relationship was found between children’s education status and the perceived helpfulness of the allowance (P < 0.001), particularly among joint families and larger households. In terms of health, 60.6% of respondents reported poor physical and mental health, and 96.1% spent their allowance on treatment. Among them, 88.9% found it helpful, especially those who were satisfied with the allowance amount (P < 0.001). A strong association was observed between health benefits and other variables such as overcoming financial crises (P < 0.001), promoting social inclusion (P < 0.001), and eliminating gender discrimination (P < 0.001). Notably, women who overcame financial crises and experienced improved social inclusion were more likely to report positive decision-making impacts (P < 0.001). Despite these gains, 11.1% of women felt their opinions remained undervalued, citing unemployment (40%), low societal importance (30%), and financial incapacity (30%) as key reasons.